Effect of mechanical ventilation on central venous pressure measurement among adult post-open heart patients - Montemayor, Maria Giselle S. (2000)
Objectives. The usual practice in CVP measurement of mechanically ventilated patients is to remove the ventilator to measure the CVP during exhalation phase. The main purpose of this study was to find an alternative but acceptable method to measure the CVP when a patient is hooked to a mechanical ventilator. The specific research objectives are as follows: (1) To determine the effect of mechanical ventilation on CVP values among adult post-open heart patients; (2) Find out if there were variations in the CVP value when taken at different phases of the respiratory cycle; and (3) To identify a certain phase in the respiratory cycle during mechanical ventilation which coincides with the end-exhalation CVP measured during spontaneous breathing.Design. This study utilized a quasi-experimental design. This design was utilized because the independent variable was manipulated in terms of the setting of mechanical ventilator and measured at the inspiratory and expiratory phases of respiration.Sampling. Subjects of this study included adult post-open heart patients in a tertiary hospital. These patients were selected because these patients were routinely hooked to a mechanical ventilator with a hemodynamic monitoring line post-operatively. Also, these patients follow the same course of treatment and recovery. All patients aged 18 and above, and scheduled for open-heart surgery were included in the study. Patients were excluded if the CVP line was malfunctioning (determined by the right atrial waveform display via a hemodynamic monitor and catheter tip placement confirmed by x-ray); and if the participant was hemodynamically unstable (BP 90 mm Hg and 150 mm Hg and CR 60/min or 120/min). Of the twenty-five (25) post-open heart patients, only thirteen (13) patients qualified and finished the data gathering procedure.All CVP values were measured manually via a print out of the CVP waveform using a strip chart recorder located at the nurses' station. All hemodynamic pressures utilized the transducer system of monitoring connected to a flushing device and a hemodynamic monitor.Data gathering. Data gathering began once the patient exhibited eye opening and/or movement of extremity. A 10-minute stabilization period followed thereafter before measurements were started. For each patient, data were collected in two (2) phases. The first phase sought to determine if there were fluctuations in CVP during undisturbed conditions. CPV was measured every 5-minutes over a 25-minute period. The second phase sought to compare CVP on ventilator and CVP with spontaneous breathing (off ventilator). In this phase, CPV was measured sequentially on-ventilator, off-ventilator, post-off ventilator, 1-minute after, 5-munites after and 10-minutes after. Two values were extracted for each ventilator setting, i.e. inhalation CVP and exhalation CVP (the two phases of the respiratory cycle). Three sets of data were gathered for each participant.To control extraneous factors that may similarly affect CVP values and to ensure patient's safety throughout the data collection procedure, a stabilization period was allowed before the measurement of CVP. Ten minutes were allowed for any change in the patient's position, 2-minutes if the patient coughed within 2-minutes of the next CVP reading, and 5-minutes if endotracheal/nasotracheal occurred within 5-minutes of the next CVP reading. If the patient was on positive expiratory end pressure (PEEP), the level of PEEP was subtracted from the actual value of the on-ventilator CVP during the exhalation phase.Data Analysis. Mean CVPs were computed for each participant and subjected to statistical treatment. In phase I, after subjecting the data to a One-way Repeated Measures ANOVA, no significant differences (a0.05) were observed in the CVP values.
Results in phase I, a comparison between CVPs measured during inhalation phase and exhalation phase was done using a paired t-Test. Result showed that there was a significant difference between these two phases despite the absence of ventilator manipulation (p=0.001). this indicates that the phases of respiration affect CVP specifically in mechanically ventilated patients.In phase II, comparing CVPs on the off-ventilator, there was statistical difference (paired t-Test, p=0.022) during the exhalation phase (p=0.428). These findings showed that no difference exists when CVPs are measured with or without the ventilator as long as CVP is measured during the exhalation phase.CVP measured during the inhalation and exhalation phases were significantly differently with taken on-ventilator (p=0.000). No significant differences in CVPs were observed when inhalation and exhalation phases were compared while off-ventilator (p=0.727). These findings supported the results obtained in phase I wherein CVP significantly fluctuated in inhalation phase. On the other hand, when patients were off-ventilator, which approximates spontaneous breathing, no differences were observed in CVPs during inhalation and exhalation phase. Thus, timing in CVP measurement when spontaneously breathing is not as crucial as those who are mechanical ventilator.CVPs measured on-ventilator in both respiratory phases had a strong and significant correlation with the CVP value off-ventilator at exhalation phase (r=0.927, significant at a=0.01). a weak correlation was observed when those values were correlated with CVPs off-ventilator at inhalation phase (inhalation r=0.463). although inhalation is positive pressure breathing ahs the same effect as that of exhalation in spontaneous breathing, these findings support more the previous findings of this study that CVP can be measured with the ventilator provided it is taken during end-exhalation phase.To determine effect on CVP after disconnecting the mechanical ventilator, CVP values measured after removing the ventilator were noted were compared to the CVP value before removing the ventilator, changes were noted when comparing the baseline and the fifth (5th) minute CVP in inhalation phase only. Again no significant changes were observed in exhalation phase. From these findings, it maybe inferred that CVP is most stable during exhalation phase than in the inhalation phase.
Conclusion: There was difficulty drawing conclusions from the results of this study due to a limited number of subjects. Nevertheless, the following conclusions are tentatively offered: (1) Mechanical ventilation has an effect on CVP but this is mediated by respiration. On inhalation, CVP tends to be higher and on exhalation, CVP returns to baseline; (2) CVPs taken during the inhalation phase were significantly affected by changes in mechanical ventilator setting, whether on, off, or upon reconnection of patient to the mechanical ventilator. These indicate that CVP taken on inhalation is highly variable and maybe affected by a number of external factors; (3) CVPs taken at end-exhalation remained generally the same whether the patient was connected to the mechanical ventilator or not. The CVP value was more constant compared to CVP taken on inhalation; (4) CVP taken on the end-exhalation while the patient is on mechanical ventilation approximates CVP taken on end-exhalation during spontaneous breathing (patient off-mechanical ventilation); and (5) CVP can be measured without removing the ventilator provided that it is read at the point of end exhalation. With all of these findings, there is enough evidence to question the practice of removing the patient from the ventilator just to measure the CVP.Recommendations. Based from the findings of this study, the researcher recommends the following: (1) Standardization of CVP measurement in patients on mechanical ventilation and on CVP transducer system should be done, wherein CVP can be measured with the ventilator provided it is measured during the exhalation phase; (2) Three approaches for future researches may be done to validate the findings of this study: (a) Replication of this study should be done with a large sample size with a similar population and the same type of CVP monitoring system (transducer system); (b) Other patient population should be investigated but measures should be done to make the subjects as homogenous as possible since CVP can be affected by a lot of factors including the patient's condition; and (c) The study should be applied to water mamometer which is another type of measuring CVP; and (3) Another issue of concern of this study includes determining the minimum stabilization period before pressure measurements after position changes, turning and even suctioning.Based on the findings of this study, the CVP measured with the ventilator at exhalation phase closely approximates the CVP off-ventilator during exhalation phase. The practice of disconnecting the patient from the ventilator during CVP measurements may not have sufficient basis, that it maybe avoided by reading CVPs at end-exhalation phase while on ventilator, thus, negating the risks.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Mechanical ventilation; Central venous pressure measurement